2020
DOI: 10.3390/su13010321
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain-Based Implementation of Building Information Modeling Information Using Hyperledger Composer

Abstract: With the advancement of Building Information Modeling (BIM) technology, BIM gains more importance and becomes a prerequisite in building projects. BIM is useful throughout a building lifecycle; from building bid, design, construction, completion, operation, and maintenance to building demolition. However, current information exchange surrounding BIM is still limited and bound to a single participant or organization and is also limited to a particular phase in the building lifecycle. This paper aims to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…Suliyanti and Sari [41] demonstrate by simulation how information exchange can be secured on a blockchain for a BIM project using Hyperledger Fabric. A framework is presented by Oliveira Júnior et al [42] for the architecture of a blockchain-based information validation system that incorporates IoT, BIM and smart contracts designed to increase the confidence of information flows in projects.…”
Section: General Information Managementmentioning
confidence: 99%
“…Suliyanti and Sari [41] demonstrate by simulation how information exchange can be secured on a blockchain for a BIM project using Hyperledger Fabric. A framework is presented by Oliveira Júnior et al [42] for the architecture of a blockchain-based information validation system that incorporates IoT, BIM and smart contracts designed to increase the confidence of information flows in projects.…”
Section: General Information Managementmentioning
confidence: 99%
“…The integration of BC and BIM in information management during the life cycle of buildings brings two main benefits: (1) the transition process from BIM to BC will be easier and more efficient; and (2) data security can also be ensured during the construction phase of real estate [54]. Moreover, BIM enhanced by BC improves the security of information system across the whole life cycle of a building [55][56][57]. BC also has the potential to solve problems and challenges in the integration of LIM and CIM.…”
Section: Htd and Blockchain (Bc) Enhanced Information Modeling (Im)mentioning
confidence: 99%
“…To address the problem of information exchange in construction projects, Suliyanti [78] proposed a system for multiple interested parties to exchange construction information (Fabric, composter). In Figure 44, it is shown that the system developed a system for bidding construction projects and stores the whole cycle of construction completion in Hyperledger.…”
Section: Smart Construction Projectmentioning
confidence: 99%